PH‐Specific Halide‐Dependent Materials from ZrIV/Hydroxycarboxylic Acid/Aromatic Chelator Reactivity: Architecture–Lattice Dimensionality and Spectroscopic Fingerprint Relations. Issue 4 (8th January 2015) - Halevas, Eleftherios; Karamelidou, Asimenia; Hatzidimitriou, Antonios; Mateescu, Constantin; Salifoglou, Athanasios
Abstract: The chemical reactivity of binary and ternary Zr IV /hydroxycarboxylic acid/(N, N‐aromatic chelator) systems (hydroxycarboxylic acid = citric, malic acid; N, N‐aromatic chelator = 1, 10‐phenanthroline) has been investigated in a pH‐specific manner, giving rise to the new binary and ternary crystalline materials [Zr2 F6 (C6 H4 O7 )2 ](CH6 N3 )6 · H2 O (1 ), [Zr2 F6 (C4 H3 O5 )2 ](NH4 )4 · 3H2 O (2 ), [Zr2 (C4 H3 O5 )2 (C4 H4 O5 )2 (C4 H5 O5 )2 ](CH6 N3 )4 · 4.5H2 O (3 ), and [Zr2 (C4 H3 O5 )2 (C4 H4 O5 )2 (C4 H5 O5 )2 ](C12 H8 N2 )(C12 H9 N2 )2 (CH6 N3 )2 · 6H2 O (4 ). Compounds1 –4 were characterized by elemental analysis, FTIR spectroscopy, TGA, 13 C‐CPMAS, 19 F‐DPMAS, and 1 H CRAMPS NMR spectroscopy, and X‐ray crystallography. The structures of1 –4 reveal the influence of fluoride in the starting Zr IV reagents on the identity of the Zr2 O2 ‐containing dinuclear assemblies in the arisen 3D architectures. The uniquely defined spectroscopic data, including the NMR data, corroborate the X‐ray structures of1 –4 and reflect the contribution of the intra/intermolecular interactions to the structural speciation of the investigated systems. Collectively, the work 1) depicts the factors that determine the nature and properties of the emerging synthetic materials in the investigated systems, 2) formulates structural architecture–lattice dimensionality and spectroscopic fingerprint correlations, and 3) projects the framework through which new Zr IV materials with defined physicochemical properties can arise at the binary and ternary level. Abstract : The pH‐specific reactivity of binary/ternary Zr IV /citric (malic) acid/(phenanthroline) systems leads to inorganic/organic hybrid Zr2 O2 ‐containing dinuclear assemblies with distinct 3D architectures. Structural speciation reveals the influence of halide on the ultimate structure and well‐defined factor correlations earmarking spectroscopic identity in the design of advanced materials.